2016
DOI: 10.1007/s10661-016-5468-z
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal contaminations in soil-rice system: source identification in relation to a sulfur-rich coal burning power plant in Northern Guangdong Province, China

Abstract: Heavy metal contents (As, Cd, Cr, Cu, Hg, Ni, Pb, and Zn) in 99 pairs of soil-rice plant samples were evaluated from the downwind directions of a large thermal power plant in Shaoguan City, Guangdong Province, China. Results indicate that there is a substantial buildup of As, Cd, Cu, Pb, and Zn in the predominant wind direction of the power plant. The significant correlations between S and heavy metals in paddy soil suggest that the power plant represents a source of topsoil heavy metals in Shaoguan City due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…Cu, Pb, and Zn were the major constituents of ore minerals and could be discharged into surrounding soils via atmospheric deposition accompanying with the mining activities (Lu et al, 2015). In the present study, MF soils were seriously polluted by HMs because the surrounding mining activities have lasted for decades, consistent with previous studies (Wang X.Q. et al, 2016; Leung et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Cu, Pb, and Zn were the major constituents of ore minerals and could be discharged into surrounding soils via atmospheric deposition accompanying with the mining activities (Lu et al, 2015). In the present study, MF soils were seriously polluted by HMs because the surrounding mining activities have lasted for decades, consistent with previous studies (Wang X.Q. et al, 2016; Leung et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…For instance, in Shaoguan, the pollution level of rice is far greater than the maximum permissible limit (0.2 mg/kg) for the average concentration of Cd (0.69 mg/kg) and Pb (0.39 mg/kg), elevating the risk of these metals entering the human body. 54 , 65 …”
Section: Methodsmentioning
confidence: 99%
“…Although numerous studies have reported the impacts of toxin concentration and other parameters on the OUR or other indicators representing the activated sludge activities [27,28,32], our work is the first attempt to explain the toxic effects in a theoretical model, and the results suggested that toxic substances, MLSS and HRT were all key factors affecting the ROUR.…”
Section: Toxicity Model Predicting the Rour Under Different Conditionsmentioning
confidence: 80%
“…Biological monitoring is an alternative approach to evaluate the influent quality by assessing the toxicity, instead of the accurate composition of wastewater [24]. Many studies on biological early-warning systems use various indicators to monitor the influent toxicity in WWTPs, e.g., animals and plants [25,26], special bacterial strains [27,28], microbial current [29][30][31], and respiratory rate [32]. Among them, luminescent bacteria are widely studied [33][34][35] but suffer from the difficulties in online cultivation and monitoring [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%